Numerical simulation of cell squeezing through a micropore by the immersed boundary method. (February 2018) - Tan, Jifu; Sohrabi, Salman; He, Ran; Liu, Yaling
The deformability of cells has been used as a biomarker to detect circulating tumor cells from patient blood sample using microfluidic devices with microscale pores. Successful separations of circulating tumor cells from a blood sample require careful design of the micropore size and applied pressure. This paper presented a parametric study of cell squeezing through micropores with different size and pressure. Different membrane compressibility modulus was used to characterize the deformability of varying cancer cells. Nucleus effect was also considered. It shows that the cell translocation time through the micropore increases with cell membrane compressibility modulus and nucleus stiffness. Particularly, it increases exponentially as the micropore diameter or pressure decreases. The simulation results such as the cell squeezing shape and translocation time agree well with experimental observations. The simulation results suggest that special care should be taken in applying Laplace–Young equation to microfluidic design due to the nonuniform stress distribution and membrane bending resistance.